Burkina Faso : 2018 Article IV Consultation; First Review Under the Extended Credit Facility Arrangement; Request for Waiver for Nonobservance of a Performance Criterion, and Modification of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2019)
Burkina Faso faces large social and physical infrastructure gaps, a deteriorating security situation, and unease among the rapidly-expanding population about economic prospects. Growth has been robust, averaging more than 6 percent over the past two years. Activity has been supported by expansionary fiscal policy, including from a boost to capital spending in 2017. Revenue has not increased as expected and the wage bill has been rising.